Feedback on system or operator performance: Which is more useful for the timely detection of changes in reliability, trust calibration and appropriate automation usage?. (November 2019) - Lu, Yidu; Sarter, Nadine
Creating safe human-machine systems requires that operators can quickly notice changes in system reliability in the interest of trust calibration and proper automation usage. Operators' readiness to trust a system is determined not only by the performance of the automation but also by their confidence in their own abilities. This study therefore compared the usefulness of feedback on the performance of either agent. The experiment required two groups of ten participants each to perform an automation-assisted target identification task with "Automation Performance Feedback" (APF) or "Operator Performance Feedback" (OPF). Four different scenarios differed with respect to the degree and duration of changes in system reliability. Findings indicate that APF was more effective for supporting timely adjustments of perceived system reliability, especially with large and long reliability changes. Subjective trust ratings and performance were not affected, however, suggesting that these two factors are closely linked and more relevant for automation reliance.